Evaluation of Sales Accounting Information Systems in Improving the Effectiveness of Accounts Receivable Control - Saleh, Erdha Nafayta Austin; Sutisman, Entar; Kartim, Kartim (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: The purpose of this study is to investigate the implementation of a well-structured sales accounting information system in controlling company receivables at PT Tabi Anugerah Pharmindo. Research Design and Methodology: The research design includes an analysis of the characteristics of the COSO internal control system applied in credit risk management. The research methodology involved data collection through interviews and observations of the company's sales and accounts receivable collection processes. Findings and Discussion: The primary findings of this study reveal that, despite the company's implementation of suitable control measures, challenges persist, particularly in managing receivables from government institutions and certain pharmacies. Implication: The implications of this study highlight the importance of integrating internal control mechanisms with sales accounting information systems to manage credit risk more effectively. Recommendations for further research include the development of a more integrated control model and a study on the application of the latest technology in managing company receivables.